Corneal keloid: four case reports of clinicopathological features and surgical outcome. Issue 1 (December 2016) - Lee, Hyo; Choi, Hyuk; Kim, Mee; Wee, Won; Oh, Joo
Abstract Background Surgical outcome of corneal keloid is largely variable depending on reports, although surgical management is inevitable in visually significant cases. We here report clinical features, histopathological findings, and surgical outcome of four cases of corneal keloid. Case presentation Four Korean male patients without a history of corneal trauma or disease were clinically and histologically evaluated for a slowly-growing, white opacity in the cornea. On slit lamp examination, corneal lesions appeared as a solitary, pearly white, well-circumscribed nodule with a smooth and glistening surface. Because the lesions involved the visual axis deteriorating the visual acuity, the nodules were surgically removed by superficial keratectomy in all patients. Amniotic membrane transplantation was combined in three patients, and an intraoperative mitomycin C application in two patients. Hematoxylin-eosin staining of the excised nodules revealed epithelial hyperplasia, Bowman's layer disruption, thick and irregularly-arranged collagen fibers in the stroma, and accumulation of prominent fibroblasts, which are consistent with the diagnosis of corneal keloid. The corneal keloids recurred in all patients within 10 months of surgical excision and outgrew the boundary of the excised area. Conclusion A diagnosis of corneal keloid should be suspected in patients presenting with an enlarging, white, glistening corneal nodule, even in the absence of a history of corneal trauma or disease. The recurrence is common after surgical excision, and the lesion can be exacerbated by surgery.